ANALYSIS OF THE PRACTICE OF EXEMPTION FROM CRIMINAL LIABILITY WITH THE APPOINTMENT OF A JUDICIAL FINE BY THE COURTS OF THE PRIMORSKY REGION - M. A. Khrebtova; Ya. V. Tarasova (Теоретическая и прикладная юриспруденция)
The practice of liberation from criminal responsibility with the appointment of a judicial ﬁne by the courts of the Primorsky region is generalized. The reasons for the application or refusal to apply a criminal-law arrangements in the form of a judicial ﬁne are considered. The analysis correlates with the general Russian trend and can be used to assess the applicability of this legal norm when making decisions in criminal cases.